Chapter Amori proibiti in palazzo Mondragone Carnesecchi. Un'inedita cupola di Antonio Puglieschi e una memoria medicea - Betti, Marco (Studi e saggi, 2020)
The recent discovery of a dome painted by Antonio Puglieschi in the Mondragone Carnesecchi palace, representing Mars and Venus surprised by Vulcan, offers the occasion to reflect on the symbols used by Francesco I de' Medici and Bianca Cappello. According to an ancient rumor, the clandestine love encounters between Francesco and Bianca had taken place in that very same palace and the depiction of the mythological infidelity may alluded to that relationship. The paper analyses different sources which show that Francesco was often portrayed as Mars and Bianca as Venus: specific attention is given to the detailed description of their wedding celebrations which revolved around the theme of the meeting and love of Venus and Mars. It's possible that the Del Vernaccia family, who owned the palace and commissioned the painting to Antonio Puglieschi, wanted to remember and somehow celebrate events that took place in those rooms more than a century before.